THE EFFECTIVENESS OF ROUND ROBIN SUMMARIZING ON READING COMPREHENSION FOR THE TENTH GRADES STUDENTS OF SMA NAHDLATUL ULAMA 2 GRESIK - Sholihah, Khilayatus (Jetlal, 2017)
Reading has an important role towards speaking in which speaking needs much vocabulary knowledge to develop ideas in communication. By reading activity readers can obtain much information. English as foreign language has some aspects in learning it. So, the aspect can be mastered by appropriate strategy. One of the strategies is round robin summarizing technique. Round robin summarizing can be one of strategy in learning reading skill. The purpose of this research is to investigate the significant effect of round robin summarizing in reading skill for 10th grade students at SMA Nahdlatul Ulama 2 Gresik in academic year of 2016/2017. In this research, the researcher used quantitative research and it refers to experimental research design because the purpose of the research is to investigate the effect of round robin summarizing on students’ reading comprehension. This research started during December, 2016. The population of this research was the tenth grade students of SMA Nahdlatul Ulama 2 Gresik. Because the population is large the researcher decided to use cluster sampling technique to select two classes with the same ability. Two classes were taken as the sample of the research. Those are X-A as the experimental group and X-B as the control group. The data tested using t-test formula by comparing the mean score of pre-test and post-test from both of classes. The result of post-test score mean showed that experimental group was higher than control group. The post-test score mean of the experimental group was 58.67 while the control group was 53.12. The result of this study showed that probability value both of the groups was 0.000 (0.000 < 0.005). This result showed that the experimental group and the control group were different in their ability after giving treatment. So, the null hypothesis could be rejected. Then, the null hypothesis stated that there was significant different using round robin summarizing towards students’ reading comprehension between experiment and control groups. Based on the description above, the researcher found that there was significant different in reading comprehending between the students who were taught using round robin summarizing and who were taught without using round robin summarizing. Having known from the finding of the study, it was indicated that round robin summarizing significantly influence towards students’ reading comprehension of students at SMA Nahdlatul Ulama 2 Gresik. For further researcher, the researcher hopefully round robin summarizing can be used in different skill.